Review of the land subsidence hazard in Pekalongan Delta, Central Java: insights from the subsurface (Rudarsko-geološko-naftni zbornik, 2021)
Land subsidence is a global threat to coastal areas worldwide, including the North Java coastal area. Of many areas experiencing land subsidence in North Java, the rate of land subsidence in Pekalongan has matched the high subsidence rates usually found in big cities. The rate of land subsidence in Pekalongan far exceeds the sea-level rise, resulting in a looming threat of land loss. The devastating impacts of land subsidence are the manifestation of its subsurface movement. Therefore, it is essential to understand the subsurface to elucidate the mechanism of land subsidence. Previous studies on land subsidence in Pekalongan are mainly related to subsidence rate monitoring and have not elaborated on the subsurface condition. This paper reviews the Pekalongan subsurface geology based on available literature to provide insight into the land subsidence problem. The results revealed that the land subsidence occurs in the recent alluvial plain of Pekalongan, consisting of a 30-70m thick compressible deposit.Possible mechanisms of land subsidence arise from natural compaction, over-exploitation of confined groundwater, and increased built areas. As the seismicity of the study area is low, tectonic influence on land subsidence is considered negligible. It is expected that the offshore, nearshore, and swamp deposits are still naturally compacting. As the surface water supply is minimal, over-exploitation of groundwater resources from the deltaic and Damar Formation aquifers occurs. In the end, future research direction is proposed to reduce the impacts of the subsidence hazard.